Smoking cessation and attempted cessation among adults in the United States. - Amir Goren; Kathy Annunziata; Robert A Schnoll; Jose A Suaya (PLoS ONE)
Aims With growing recognition of stagnant rates of attempted cigarette smoking cessation, the current study examined demographic and psychometric characteristics associated with successful and attempted smoking cessation in a nationally representative sample. This additional understanding may help target tobacco cessation treatments toward sub-groups of smokers in order to increase attempts to quit smoking. Design, setting, and participants Data were used from the 2011 U.S. National Health and Wellness Survey (n = 50,000). Measurements Current smoking status and demographics, health characteristics, comorbidities, and health behaviors. Findings In 2011, 18%, 29%, and 52% of U.S. adults were current, former, or never smokers, respectively. Over one quarter (27%) of current smokers were attempting to quit. Current smokers (vs. others) were significantly more likely to be poorer, non-Hispanic White, less educated, ages 45-64, and uninsured, and they had fewer health-conscious behaviors (e.g., influenza vaccination, exercise). Attempting quitters vs. current smokers were significantly less likely to be non-Hispanic White and more likely to be younger, educated, insured, non-obese, with family history of chronic obstructive pulmonary disease, and they had more health-conscious behaviors. Conclusions Smokers, attempting quitters, and successful quitters differ on characteristics that may be useful for targeting and personalizing interventions aiming to increase cessation attempts, likelihood, and sustainability.